West Ham Blind Xmas Dinner Fund (circular ; accounts) - West Ham Trades Council ; West Ham League of the Blind; Pearmaine, L. H. (1929)
1929 1929 1920s 2 pages THE WEST HAM LOCAL BLIND XMAS DINNER FUND. (Supported by the Mayor of West Ham, local Members of Parliament and other local organizations.) SECRETARY & TREASURER. L.H.PEARMAINE. 16, KING STREET. PLAISTOW.E.13. INCOME. £. s. d EXPENDITURE. £ . s. d Balance 1927. 5 9 0 West Ham Trades Council 3 18 0 Rev. Kennedy Cox. 1 1 0 London Co-op Society. 10 6 Plaistow Workman's Club. 10 6 Captain Holt M.P. 1 1 0 The Mayor. Alderman Bell. 1 1 0 Printing. Postage & J.G.Storey. " The Trossachs 10 6 Mann Crossmann & Paulin. 10 6 1 14 6 Messrs Bryant & May, per Mr. Paton. 2 2 0 Sundries. 1 12 7½ West Ham Woman's Co-op Guild. 1 0 0 Custom House -do- -do- 10 0 Purchase of Calico Sheets For Football Collection. 12 10½ Alderman. W. Thorne. M.P. 1 0 0 S.F. Whitlock. W.H.T.C. 10 0 Rev Rowntree Clifford. 1 1 0 Northen Highways. C.B.W.H. 2 3 3 South West Ham. I.L.P. 10 0 One Box of Orangesper L. Refray. 9 2 T. Wicks Esq; Abbey Arms. 10 0 W.H. Evans & Sons. 10 0 W. Dipple esq: The Alexandria. 5 0 Canning Town Co-op Womens Guilds. 10 0 Cartage of Fruit from Market. 3 0 Stratford New Town -do- -do- 3 6 West Ham Football Patrons per S. King Eq; 11 18 6 Southern Highways C.B.W.H. 3 10 8 Receipts. 2 6 Patrons Imperial Cinema. 1 1 6 Patrons Playhouse Cinema 10 6 Paid over to the Blind, at Holbrook Mission. 77 16 0 Patrons The Grand Cinema. 1 6 8 Mrs. Chaplin per Collection Box. 1 8 2 Stables Dept: C.B.W.H. 3 0 0 Education Works Dept. C.B.W.H 1 18 0 West Ham & District Cricket League. 5 0 Special grants to Blind. 4 0 0 C.B.W.H. Sewerman, 1 4 0 Pumping Station C.B.W.H. 1 2 0 Mrs. Pearmaine per Collection Box. 10 1 Mr. W. Teeling. 1 0 0 Grove House Players. 4 13 6 Workers Supply Association. 1 0 0 Messrs Tate & Layle [Lyle] 2 2 0 West Ham Tramwaymen's Club. 1 1 0 Weights & Measurers C.B.W.H. 5 0 National League of the Blind W.H.B. 5 0 0 Patrons West Ham Lane Kinema. 17 9 Patrons Greengate and Park Cinemas 1 3 0 Mr. A. Simmonds per Collection Box. 18 7 Liberal & Radical Club. 1 10 6 No.6. N.A.O.P. 1 0 0 Barking Road Tradespeople. 17 0 Works Dept C.B.W.H. 18 0 Miss Harbott W.H.T.C. 5 0 West Han Trades Union Branches. 9 12 9 6 £ 85 11 5 £85 11 5 SWEETS WERE KINDLY GIVEN BY MESSRS STRIEMER & SONS. FRUIT by MESSRS FOX, GODDARD & REFRAY. L.H. PEARMAINE. Secretary. AUDITED AND FOUND CORRECT. MRS. E.V. PARKER. N.U.T. H. NASON. N.S.B.S. 292/841.4/1/62